Reinterpretasi Hadist Mesoginik Tentang Penciptaan wanita Dari Tulang Rusuk Laki-Laki - Mubaidi Sulaeman (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2020)
Islam comes when women's standing is still likened to that of objects and inferior to animals. They can be traded even inherited. Since thousands of years ago, women were placed as subordinates of men. Even from the many defences of Islamic teachings, the importance of lifting the degree of women, both in public and private spaces feels ignored, because some religious evidence (read: Qur'an and Hadith) tend to be interpreted mesoginikly. This paper is about the hadith which describes the creation of women from the ribs of men takhrij and syarah which is considered mesoginik. The hadiths chosen are those narrated by al-Bukhaari, Muslim, Ahmad Ibn Hambal and Tirmidhi in tahrij to raise the degree of hadith to a higher degree of legal force. In addition, in this paper, the author wants to explain the understanding of these hadiths in the frame of feminism. The opinions of feminists such as Amina Wadud and Rifat Hasan, it is important today to be heard as a counterweight to the religious interpretations that have tended to be mesoginic.